Clinically ulcerated and granulomatous pilomatricoma in a cutaneous vaccination site: case report - Rodrigo Scabora; João Gabriel Rodrigues Alberti; Carolina Scaf Haddad Bartos; Lucia Mioko Ito; Ayrton Roberto Pastore; Deborah Krutman Zveibil (Sociedade Brasileira de Dermatologia (SBD), 2022)
Pilomatricoma is a benign skin tumor derived from the hair follicle. It has a varied etiology, and the traumatic one is often described as a triggering factor. The surgical treatment is curative and, therefore, the choice. We report a case of an atypical clinical presentation pilomatricoma - an ulcerated nodule topped by a central hematic crust, with peripheral telangiectasias probably triggered by the HPV vaccination. The ultrasound examination suggested the possibility of a chronic inflammatory granuloma, although the histopathological examination was definitive and confirmed the diagnosis of pilomatricoma.